1997
DOI: 10.1136/gut.41.4.545
|View full text |Cite
|
Sign up to set email alerts
|

Are complications of endoscopic sphincterotomy age related?

Abstract: Background-Endoscopic retrograde cholangiopancreatography sphincterotomy is increasingly performed in younger patients undergoing laparoscopic cholecystectomy. However, the safety of endoscopic sphincterotomy in this age group, relative to that in older patients, is unknown. Aim-To determine whether the development of short term complications following endoscopic sphincterotomy is age related. Patients and methods-A prospective multicentre audit of 958 patients (mean age 73, range 14-97, years) undergoing a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
3
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 13 publications
(9 reference statements)
1
27
3
6
Order By: Relevance
“…However they have certain limitations. Deans et al and Agarwal et al included outcomes in patients as young as 60 years of age [9,10]. In contrast, the mean age in our study was 84.7 years for males and 85.1 years for females.…”
Section: Discussioncontrasting
confidence: 50%
“…However they have certain limitations. Deans et al and Agarwal et al included outcomes in patients as young as 60 years of age [9,10]. In contrast, the mean age in our study was 84.7 years for males and 85.1 years for females.…”
Section: Discussioncontrasting
confidence: 50%
“…In general, the rate of patients with a hemorrhagic tendency is higher among older patients than among younger patients. Accordingly, a higher age is a risk factor for post-EST hemorrhage [17]. However, in the present study EBD without EST was conducted as the initial treatment in two patients with a hemorrhagic tendency, and then elective EST was carried out after amelioration of the hemorrhagic tendency.…”
Section: Discussionmentioning
confidence: 95%
“…Lack of ETCO2 monitoring is one of the limitations of our study. According to the , chronological age alone isn t a contraindication for ERCP or a risk factor for ERCP-related complications [13]. It has been reported that frequency of failure, hypoxia, and bleeding due to sphincterotomy is increased by advancing age and that clinicians should be more careful foralert to complications in elder individuals [14], although it was shown that ERCP can be safely employed for diagnostic and therapeutic purposes in elder individuals in addition to infants and, children and elder individuals [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%